Tropical Cyclone Intensity Modeling Using the Dvorak Technique Based on Satellite Observations - Yuli Fitria; Pakhrur Razi (EarthCare, 2026)
Tropical cyclones are among the most destructive atmospheric phenomena in tropical and subtropical regions, producing extreme winds, heavy rainfall, storm surges, and severe socio-economic impacts. Accurate estimation of tropical cyclone intensity is therefore essential for disaster risk reduction, particularly over oceanic regions where in-situ observations are limited. This study examines the temporal evolution of tropical cyclone intensity using the Dvorak Technique applied to satellite infrared and visible imagery during the period 27–29 November 2017. Distinct cloud structural patterns, including Curved Band, Central Dense Overcast, Embedded Center, and Eye Pattern, were systematically identified to derive T-numbers and Current Intensity (CI) values. These intensity estimates were converted into maximum sustained wind speeds using standard Dvorak–NOAA conversion tables. The results indicate a clear intensification sequence from a weak tropical system (T2.0) to a mature cyclone reaching a peak intensity of T5.5, corresponding to a maximum sustained wind speed of approximately 102 knots (≈188 km h⁻¹). A pronounced rapid intensification phase was detected, characterized by an increase exceeding 30 knots within a 24-hour period. The strong correspondence between cloud structural evolution and intensity variability confirms the robustness of the Dvorak Technique for tropical cyclone modeling and hazard assessment in data-sparse tropical regions.